Exploring The Management Of Community Radio In The Digital Era: A Case Study Of Radio Bamba - Ata Fudholi; Aryo Subarkah Eddyono (International Journal Labs, 2025)
Amid the pressure of digitalization and a lack of structural support, community radio in Indonesia is struggling to survive as a voice space for citizens. This study examines the sustainability strategy of community radio that is still active and adaptive in the midst of the challenges of the times, namely Radio Bamba (Balaraja). Radio Bamba is a representation of an alternative form of community-based media that relies on the values of participation, solidarity, and local culture. Through a qualitative approach with in-depth interview techniques with managers, broadcasters, active listeners, and representatives of the Indonesian Community Radio Network (JRKI), this study found that adaptation to social media was carried out in a contextual and gradual manner. Radio Bamba, with its network of young managers and a digital entertainment approach, leverages channels such as YouTube and WhatsApp to expand participation. Regulatory pressures and limited resources have led to the emergence of defensive strategies that are informal, but still ethical according to community standards. These findings show that the resilience of community radio is not only in its technological capacity, but in its social power and long-term commitment that grows from affective relationships with citizens. By placing social media as a bridge, not a destination, community radio still has a meaningful living space amidst an increasingly automated media landscape.